Analysis of Financial Performance Using Profitability Ratio Approach at PT Campina Ice Cream Industry TBk for the Period 20222024 - Suryati, Suryati; Mursida, Mursida; Mukmainna, Mukmainna; N, Ginaya Anastasya; Pongamangatta, Datu (Universitas Syiah Kuala, 2025)
This study aims to analyze the financial performance of PT. Campina Ice Cream Industry Tbk for the period 20222024 using profitability ratios, including Return on Assets (ROA), Return on Equity (ROE), Gross Profit Margin (GPM), Operating Profit Margin (OPM), and Net Profit Margin (NPM). The research employs a descriptive quantitative method using secondary data obtained from the companys official financial statements. The results indicate that the companys financial performance has fluctuated over the observed period. The average ROA and ROE were 10.68% and 12.21%, respectivelyboth below the industry benchmark, indicating suboptimal utilization of assets and equity. Similarly, the average OPM and NPM were 13.49% and 10.11%, showing inefficiencies in operational cost control and net profitability. On the other hand, the company demonstrated a relatively strong GPM with an average of 57.57%, suggesting efficiency in managing production costs. Overall, the findings suggest that PT. Campina Ice Cream Industry Tbk needs to enhance its financial efficiency through improved asset management, tighter cost control, and the implementation of more effective marketing strategies to ensure sustainable profitability and competitiveness in the future.